2006
DOI: 10.1097/01.brs.0000229228.62627.75
|View full text |Cite
|
Sign up to set email alerts
|

The Length of the Cervical Cord: Effects of Postural Changes in Healthy Volunteers Using Positional Magnetic Resonance Imaging

Abstract: We found posture-dependent differences of the length of the cervical cord in the recumbent and erect series. These results may be important when assessing the dynamic factor in cervical spondylotic myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…MRI studies have measured the cord length in cervical flexion, extension, and neutral position in healthy [17] and CSM [18] patients. These studies consistently reported lengthening of the cord in flexion as compared to neutral or extension.…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies have measured the cord length in cervical flexion, extension, and neutral position in healthy [17] and CSM [18] patients. These studies consistently reported lengthening of the cord in flexion as compared to neutral or extension.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kuwazawa et al [9, 10] demonstrated the dynamic effects of postural changes on the cervical cord using positional MRI.…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9][10][11] It may also help in understanding the true nature of spinal pathologies. In addition, it can demonstrate the mobility of each motion segment and finally, relate the mobility to the changes in sagittal alignment and disc degeneration.…”
mentioning
confidence: 99%